Ontogenetic structure and seed productivity of Arnica montana L. in the Ukrainian Carpathians - Dubliak, Andrii; Riznychuk, Nadiia; Gniezdilova, Viktoria (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2024)
The article examines the ontogenetic structure and seed productivity of Arnica montana L. in the natural conditions of the Ukrainian Carpathians, which are key aspects for understanding the dynamics of its populations and ecological adaptations. The main factors affecting population viability have been identified, including climatic conditions, altitudinal zonation, phytocenotic state, and the intensity of anthropogenic impact. An analysis of the spatial distribution and age structure of populations has been conducted, allowing for an assessment of the species' adaptive potential and its capacity for natural regeneration. The relationship between altitudinal zonation, plant community structure, and seed renewal indicators has been studied. The obtained data confirm that the presence of favorable environmental conditions is a determining factor in ensuring the successful regeneration of the species. It has been established that in the conditions of mid-mountain meadows and the subalpine zone, Arnica montana L. exhibits a higher level of seed productivity compared to high-mountain areas, where a gradual decline in potential seed productivity is observed due to ecological constraints. The phase development of Arnica montana L. individuals at different ontogenetic stages has been analyzed. A quantitative analysis of potential and actual seed productivity indicators, as well as seed regeneration levels in different ecological niches, has been conducted. A set of measures for the conservation of natural populations of Arnica montana L. in the region has been proposed. These measures include limiting livestock grazing, regulating recreational impact, prohibiting the collection of medicinal raw materials in natural habitats, and protecting key populations in protected areas. The possibility of creating artificial populations and restoring the species in areas of its historical distribution is also considered.